Hubungan Kecerdasan Emosional terhadap Tingkat Depresi Mahasiswa Fakultas Kedokteran Universitas Tarumanagara - Teddy Tjahyanto; Ni Kanaya; Grace Keren; Eunike Angellina Mulyadi; Kevin Sanjaya Listiono (Syntax Corporation Indonesia, 2021)
The World Health Organization (WHO) recognize the COVID-19 pandemic as an imminent global threat. To dampen the spread of the highly-contagious virus, the Indonesian government has imposed several social-distancing and government regulations. Nonetheless, these regulations result in peripheral effects; many people are subject to loneliness, fear, and anxiety—all of which leads to depression. Statistical evidence show that depression is very much prevalent in Indonesians—reaching a staggering 62% as of August 2020. Multiple studies have proven the negative correlation between emotional intelligence—which is the ability to regulate and control emotions—and depression. Consequently, this study aims to determine the relationship between emotional intelligence and depression in medical students of Universitas Tarumanagara batch 2019. Using a descriptive analytic research design with a cross-sectional approach, we obtained data through simple random sampling a total of 154 respondents who answered an emotional intelligence questionnaire used as a proxy in determining the level of emotional intelligence. Statistical analysis using the chi-square test confirmed that there is a significant negative correlation between emotional intelligence and depression during the COVID-19 pandemic, yielding a p-value of 0.003. In conclusion, students can improve their level of emotional intelligence as a preventive measure of depression during the COVID-19 pandemic.